The translation of conjunctions in persian into English in Kimya Khatun / Seyedeh Hanieh Tavakolian - Seyedeh Hanieh , Tavakolian (2019)
Conjunctions are among the significant facets of texts in Translation Studies. They vary across languages in terms of the way and process of transferring into another language. Further, the fact that to what extent conjunctions remain implicit or undergo explicitation is of research interest in the process of translation from Persian into English. The present study aimed at investigating the translation of conjunction used in the novel of “Kimya Khatun” in terms of ST and TT differences and explicitation level, to identify the differences the model of conjunctions proposed by Halliday and Hassan (1976) was chosen as the theoretical framework, while, Blum-Kulka’s (1986) hypothesis was used to investigate the explicitation of conjunctions. The present study covered a corpus of about 54000 Persian words and 57000 English words, pertaining to seven parts of the novel and its English translation, and the comparison was made based on the descriptive, quantitative and qualitative methods. As such, the sentences in both languages were aligned and 1509 cases of conjunctions in Persian and 1305 in English were identified and tabulated for studying the effectiveness of translation of conjunctions. In addition, 500 cases of conjunctions were analyzed for explicitation. On the whole the findings revealed that there were just few differences between Persian and English conjunctions and their rendering to English was successful. Regarding explicitated cases, the results indicated that, according to Blum-Kulka’s (1986) model, from among the three categories of this model, i.e., explicitation, implicitation, and change of meaning, the explicitation accounted for 16% of cases, implicitation about 7%, and meaning change about 6% in the analyzed sample.